2022
DOI: 10.3390/cells11142192
|View full text |Cite
|
Sign up to set email alerts
|

Flightless I Negatively Regulates Macrophage Surface TLR4, Delays Early Inflammation, and Impedes Wound Healing

Abstract: TLR4 plays a pivotal role in orchestrating inflammation and tissue repair. Its expression has finally been balanced to initiate the early, robust immune response necessary for efficient repair without excessively amplifying and prolonging inflammation, which impairs healing. Studies show Flightless I (Flii) is an immunomodulator that negatively regulates macrophage TLR4 signalling. Using macrophages from Flii+/−, WT, and FliiTg/Tg mice, we have shown that elevated Flii reduces early TLR4 surface expression, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It has been shown that the use of neutralizing antibodies against Flii attenuates the inflammatory response induced by imiquimod in psoriasis mice ( 147 ). Regarding the fundamental role of the TLR4-NF-κB pathway in the pathogenesis of psoriasis ( 148 ), Flii may interfere with the binding of TLR4 to myeloid differentiation primary response protein 88 (MyD88), which thereby inhibits the NF-κB pathway ( 149 ). Resultantly, this leads to a reduction in the release of downstream inflammatory factors and a decrease in psoriasis symptoms.…”
Section: Flightless I In Psoriasis and Admentioning
confidence: 99%
“…It has been shown that the use of neutralizing antibodies against Flii attenuates the inflammatory response induced by imiquimod in psoriasis mice ( 147 ). Regarding the fundamental role of the TLR4-NF-κB pathway in the pathogenesis of psoriasis ( 148 ), Flii may interfere with the binding of TLR4 to myeloid differentiation primary response protein 88 (MyD88), which thereby inhibits the NF-κB pathway ( 149 ). Resultantly, this leads to a reduction in the release of downstream inflammatory factors and a decrease in psoriasis symptoms.…”
Section: Flightless I In Psoriasis and Admentioning
confidence: 99%
“…Both are reported to act as regulators of eukaryotic protein expression; FLI1 is a co-activator of nuclear receptor mediated transcription (e.g., estrogen receptor and glucocorticoid receptor) (30)(31)(32), while LRRF1 is a known transcriptional repressor with DNA binding activity (e.g., tnf) (33)(34)(35)(36). Both are also involved in regulating host innate immune responses to infection, though their activity has been shown to be both antagonistic and synergistic (37)(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%